Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4067/s0718-221x2013005000021
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of oscillating climates for wood drying using the flying wood test and loaded beams: need for a new mechano-sorptive model

Abstract: In this work, the effects of moisture content variations produced by oscillating drying conditions have been studied by means of non-symmetrical drying (flying wood) and loaded drying (3-point bending test). The oscillating conditions are intended to produce a mechano-sorptive creep that is able to reduce drying stresses. However, our experimental data seem to prove that the activation of the mechano-sorptive creep by oscillations of the moisture content is very limited. Besides, the simulations showed that no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Zanuncio et al (2015), found a moisture content greater than 30% in Eucalyptus and Corymbia logs after 90 days of drying. The water evaporated depends on factors such as anatomy, density, and piece dimensions (Rezende et al, 2010;Monteiro et al, 2017;Hoang et al, 2015), as well as environmental factors such as temperature, relative humidity and wind speed (Rémond et al, 2013). Few studies have assessed water flow, above and below the fiber saturation point, or the behavior of the drying curve in Round wood.…”
Section: Introductionmentioning
confidence: 99%
“…Zanuncio et al (2015), found a moisture content greater than 30% in Eucalyptus and Corymbia logs after 90 days of drying. The water evaporated depends on factors such as anatomy, density, and piece dimensions (Rezende et al, 2010;Monteiro et al, 2017;Hoang et al, 2015), as well as environmental factors such as temperature, relative humidity and wind speed (Rémond et al, 2013). Few studies have assessed water flow, above and below the fiber saturation point, or the behavior of the drying curve in Round wood.…”
Section: Introductionmentioning
confidence: 99%
“…Bending in wood can also be caused by differential expansion resulting from an asymmetric moisture content distribution. This phenomenon has been studied during kiln-drying [7][8][9][10][11], and in the case of a board simulating a painted panel [12].…”
Section: Introductionmentioning
confidence: 99%
“…doors or furniture) and reused for instruments (naturally seasoned) and (2 most common) wood left to be air-dried for several years by the instrument maker. Oscillating climates have been studied for industrial drying processes (Rémond et al 2013). A reduction in EMC and of dimensional instability after humidity cycling, due to the partial saturation of the cell wall polar groups which leaves them unreachable for water vapor, was previously reported (Garcia Esteban et al 2005).…”
Section: Table1mentioning
confidence: 99%